Evolution of AI-Powered Surveillance and Its Role in Political Control (Journal of Asian Development Studies, 2026)
This paper examines the evolution of AI-powered surveillance and its implications for political control. The rapid advancement of Artificial Intelligence (AI) has transformed the landscape of surveillance, enabling governments to monitor and control citizens with unprecedented efficacy. Researchers analyse the development of AI-driven surveillance technologies, including facial recognition, predictive analytics, and social media monitoring, and their deployment in various regimes. This research is conducted under the qualitative research methodology. Ananalytical approach is used to provide a comprehensive and analytical understanding of AI-powered surveillance technologies. The analysis reveals that AI-powered surveillance has become a crucial tool for governments to suppress dissent, monitor opposition, and maintain social control. Authoritarian regimes leverage AI-driven surveillance to identify and silence critics, while democratic governments use it to monitor citizens under the guise of national security. The use of AI-powered surveillance has significant implications for civil liberties, including the erosion of privacy, freedom of expression, and assembly. It is argued that the unchecked proliferation of AI-powered surveillance technologies poses a significant threat to global democracy and humanrights. The paper concludes by highlighting the need for robust regulations, transparency, and accountability mechanisms to prevent the misuse of AI-powered surveillance for political control. By examining the evolution of AI-powered surveillance, this paper sheds light on the emerging challenges to democracy and human rights in the digital age.